PERAN ETIKA INOVASI DAN KEWIRAUSAHAAN LEMBAGA DAKWAH DI ERA DISRUPTIF - Siti Sofiah Rahmawati; Cecep Castrawijaya (Al-Idaroh: Media Pemikiran Manajemen Dakwah, 2024)
This disruptive era has had the impact of major changes in various fields, including da'wah institutions. Da'wah institutions as religious organizations face the challenge of remaining relevant, effective, and harmonious in conveying moral and spiritual messages to society. In this context, the ethics of innovation and entrepreneurship are key to the adaptation of da'wah institutions, because they can influence people's perceptions of these institutions. This research aims to explore how da'wah institutions apply innovation ethically and how entrepreneurship can support its sustainability in a disruptive era. Using qualitative research methods, this research explores insights from various da'wah institutions through library research based on primary data sources and secondary data to examine the ethics of innovation and entrepreneurship in the context of da'wah institutions. Primary data are journals and books related to secondary data obtained from dictionaries, encyclopedias, and journal reviews. The research results show that ethical innovation and moral entrepreneurship are important factors in maintaining the relevance of da'wah institutions in a disruptive era and the role of ethics in innovation and entrepreneurship in da'wah institutions.